Smokeless tobacco quitting during COVID-19: A mixed-methods pilot study among participants screened for a cessation trial in India - Prashant Kumar Singh; Pankhuri Jain; Varsha Pandey; Shikha Saxena; Surbhi Tripathi; Anuj Kumar; Lucky Singh; Shalini Singh (Elsevier, 2021)
Introduction: COVID-19 and subsequent country-wide lockdown has impacted smokeless tobacco (SLT) product availability in India. We aimed to examine SLT quitting during COVID-19 lockdown among SLT users who consented to be enrolled in a cessation programme. Methods: Between January-March 2020, we screened 227 exclusive SLT users to be enrolled in a randomized-controlled feasibility study on SLT cessation. However, all activities were suspended due to national lockdown in response to the COVID-19 pandemic. To examine the quitting intention and behaviour during COVID-19 lockdown, we re-contacted these individuals telephonically; during September-October 2020. Results: Of 227 participants, 87 (38.3%) could not be contacted on phone. We conducted telephonic qualitative interviews and assessed the SLT use status, willingness to quit and participate in the SLT cessation trial among the remaining 140 participants. Among these, 12.1% (17/140) showed no willingness to participate in the study due to migration. Since COVID-19 lockdown, 32.1% (45/140) participants reported quitting SLT due to non-availability, increased cost of products, shifts in community norms and family pressures. Conclusions: COVID-19 pandemic presented an opportunity for tobacco cessation as stringent bans and isolation from social circles enabled tobacco cessation. It also triggered improvement in dissemination of public health information at an unprecedented scale, particularly related to the vulnerability of tobacco users to co-morbidities and harm from SARS CoV-2 infection. Implementation of strict bans on sale and consumption of SLT and strengthening of cessation support may lead to sustainable tobacco control. This study provides insight into effective policy strategies to reduce SLT use; which need to be substantiated with adequate cessation support.